PENINGKATAN KEMAMPUAN MENULIS PARAGRAF DALAM MENEMUKAN IDE POKOK DENGAN MENERAPKAN METODE INKUIRI SISWA KELAS IV SDN 2 LAEMANTA - Suparni suparni (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This study aims to describe the application of inquiry methods to improve the ability to write paragraphs of class IV of Laemanta Elementary School 2. In the study carried out two cycles, namely cycle I and cycle II with a target of a minimum average value of 75. The research design model is Kemmis and MC. Tagart, research is carried out through a process of planning, action, observation, and reflection. From the results of the increase in writing paragraphs using the Cycle I inquiry method it is known that the number of class averages of 66.50 and completeness of 30% which are categorized quite good, meanwhile, the average value in cycle II is 84% and completeness 85% is included in very good category. So with that, the results obtained have met the classical completeness criteria as specified in the research indicators of at least 75%.